Cyto-histological correlation of salivary gland lesions according to the Milan reporting system - Shireen Hamid; Muhammad Mudassar; Nida Hamid; Muhammad Sarwar Zia; Tariq Mehmood; Sadia Hameed (Journal of Rawalpindi Medical College)
Objective: The objective of this study is to correlate FNAC outcomes according to the Milan Salivary Gland Cytology Reporting System (MSRSGC)system with histopathological findings of salivary gland lesions, taking as the gold standard.